Prevention and management of complications in pelvic exenteration. Issue 11 (November 2022) - Persson, Pia; Chong, Peter; Steele, Colin W; Quinn, Martha
Abstract: Pelvic exenteration is widely recognised as the gold standard of care for locally advanced tumours of the pelvis. Surgery in pursuit of curative resection comes at the cost of significant morbidity. Perioperative complications are commonplace with the majority managed without further surgical intervention. Boundaries of resection are expanding, resulting in increasing incidence of excision of major vascular structures and bone. Optimisation of patients is paramount prior to such significant surgical insult. Specialist centres with designated multidisciplinary teams should be used whenever possible. Addressing anaemia and nutrition play a significant role in prehabilitation. Intra-operatively consideration should be given to prevention of empty pelvis syndrome, perineal reconstruction, safe control of vascular structures and minimising risk of fistulae. Post-operative complications are common however employment of enhanced recovery protocols, minimally invasive surgery and opiate sparing analgesia protocols may in time lead to improvements for patients. Enteric fistulae and urine leak remain the most devastating and risk reduction strategies should be employed. Early recognition and aggressive management of complications is essential. Graphical abstract: Image 1